The safety and clinical effectiveness of rapid infusion with CT‐P10 in patients with non‐Hodgkin's lymphoma or chronic lymphocytic leukemia: A retrospective non‐interventional post‐authorization safety study in Europe. Issue 3 (17th March 2022) - Bishton, Mark; Marshall, Scott; Harchowal, Jatinder; Salles, Gilles; Golfier, Camille; Tucci, Alessandra; Fernández, Alicia Rodriguez; Sanchez Blanco, Jose Javier; Bocchia, Monica; Kim, SooKyoung; Lee, Young Nam; Zinzani, Pier Luigi
Abstract: Rapid infusion (RI) of the rituximab biosimilar CT‐P10 is currently only an approved treatment regimen for the treatment of rheumatoid arthritis. Although both CT‐P10 and reference rituximab are known to be frequently administered using a RI regimen (≤90 min) in clinical practice, published data on the safety of RI of CT‐P10 in patients with NHL and CLL are limited. Hence, this study collected real‐world safety and effectiveness data on RI‐CT‐P10 from the medical records of 196 patients with NHL or CLL in 10 European centers, 6 months after the date of the first RI (index date); the infusion‐related reaction (IRR) rate was compared to previously published data. Ten percent (95% confidence interval 6%–15%; n  = 20/196) of patients experienced an infusion‐related reaction (IRR) on day 1–2 post‐index, which was not significantly different ( p =  0.45) to the IRR rate for rituximab described in a previous meta‐analysis (8.8%). During the observation period, 2% of patients experienced grade 3–5 IRRs and 85% ( n  = 166) experienced an adverse event (non‐IRR). The most common reason for discontinuation of first‐line CT‐P10 was planned treatment completion (81%; n  = 158). Complete response and partial response to CT‐P10 was observed in 74% ( n  = 142/192) and 22% ( n  = 42/192) of patients, respectively. The results of this real‐world study demonstrate that the safety and effectiveness profile of RI‐CT‐P10 is similar to RI of reference rituximab and therefore support the current use of RI‐CT‐P10 in patients with NHL and CLL.